Identification by Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry and Antifungal Susceptibility Testing of Non-Aspergillus Molds - Li, Ying; Wang, He; Hou, Xin; Huang, Jing-Jing; Wang, Pei-Chang; Xu, Ying-Chun (Frontiers in Microbiology, 2020)
Non-Aspergillus molds including Mucorales, Fusarium, Scedosporium, etc. consist of emerging pathogens with higher mortality in immunocomprised patients. Fifty-two isolates of genetically confirmed non-Aspergillus molds representing of 16 species from 8 genera were collected to evaluate the performance of the Bruker Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry (MALDI-TOF MS) in non-Aspergillus molds identification. Antifungal susceptibilities were determined through the CLSI M38-A2 broth microdilution method and the Sensititre YeastOne colorimetric method. The Bruker MALDI-TOF MS identified 57.7% (30/52) of isolates cultured in broth and 15.4% (8/52) of isolates cultured on solid agar media to the species level respectively according to the standard interpreting criteria. Lowering the species level cut-off value from ≥2.0 to ≥1.7 could improve the MALDI-TOF MS species level identification rate to 67.3% (38/52) for isolates cultured on solid media with a slight increase of false identification rate of 2.6% (1/38). Amphotericin B was the most in vitro fungistatic-active agent for 98.1% (51/52) of the tested non-Aspergillus molds with MICs of ≤2 µg/ml. The triazoles susceptibilities were various with MICs of 0.12 to >16 µg/ml among different species of non-Aspergillus molds. The correlation between the CLSI method and Sensititre YeastOne on antifungal susceptibility testing of non-Aspergillus molds was good with essential agreement (EA) rates of >90% to triazoles and echinocandins except amphotericin B which had a lower EA rate of 84.6%. In conclusion, favorable performance of the Bruker MALDI-TOF MS in identification of clinical non-Aspergillus isolates directly inoculated on solid agar media could be achieved with the adoption of alternative interpreting criteria. Antifungal susceptibility testing is important for non-Aspergillus molds especially when the triazoles susceptibility is wanted, and the Sensititre YeastOne is a practical and reliable method to determine the antifungal susceptibilities of non-Aspergillus molds.